„Przemija bowiem postać tego świata” (1 Kor 7,31). Dziewictwo i celibat znakiem królestwa - Bogacz, Roman (Verbum vitae, 2013)
The present article is an analysis of 1 Corinthians 7:1-40. It presents the relevance of the choice of one’s way of life, either in marriage or in celibacy. Considering the passing away of this life, St. Paul showed the Corinthians the value of virginity as a testimony of the Kingdom of God. According to the apostle, this particular form of life is the best preparation for the eternal life. It enables a person to completely devote his/her life to the preaching of the Kingdom. St. Paul chose this way of living in order to commit himself to the proclamation of the Gospel. Celibacy freed him from all concerns related to the providing for the family. The teachings comprised in the analyzed text are particularly relevant for Christians living in the early twenty-first century. 1 Cor 7: 29-31 is utterly opposed to the models of life preferred in the contemporary world. In light of this utterance, it is worth asking where we can be led by this world that has chosen a completely different way of living. It is no wonder that modern man is not able to understand the value of virginity and celibacy which are a call to conversion and a sign of the Kingdom that will be opposed.